Evaluation of Hepatic Biochemical Parameters during Antiviral Treatment in COVID-19 Patients - Felicia Marc; Corina Moldovan; Anica Hoza; Patricia Restea; Liliana Sachelarie; Laura Ecaterina Romila; Corina Suteu; Dorina Maria Farcas (Biology, 2021)
(1) Background: The antiviral treatment for COVID-19 disease started to be largely used in 2020 and has been found to be efficient, although it is not specific for SARS-CoV-2 virus. There were some concerns that it may produce liver damage or other side effects. (2) Methods: The aim of this study was to observe if antiviral therapy is affecting liver parameters or producing other side-effects in patients hospitalized for COVID-19 disease. The study included a group of patients hospitalized in the internal medicine department of Oradea Municipal Clinical Hospital, Romania, between August 2020–June 2021, diagnosed with SARS-CoV-2 viral infection by RT-PCR method or rapid antigen test. During hospitalization, patients were treated with a Lopinavir/Ritonavir (Kaletra) combination, or with Favipiravir or Remdesivir. In addition to monitoring the evolution of the disease (clinical and biochemical), also hepatic parameters were analyzed at admission, during hospitalization, and at discharge. (3) Results: In the group of studied patients, the mean value of aspartat aminotrensferase did not increase above normal at discharge, alanin aminotransferase increased, but below twice the normal values, and cholestasis registered a statistically insignificant slight increase. (4) Conclusions: In our study, we found that all three antivirals were generally well tolerated and their use did not alter liver function in a significant manner.